Evaluasi Kebutuhan Unit Filling Machine LPG Kemasan Tabung 3 KG: Studi Kasus Pada Depot LPG X - Ratna Mentari; Andian Ari Istiningrum (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2018)
LPG X Depot has three main functions to receive, store, and distribute LPG 3 kg to SPPBE, SPBE, and agencies. The distribution of LPG 3 kg has increased 39.29% during 2012-2016. Therefore, the LPG filling process using unit filling machine (UFM) has experienced high load from year to year. This research has objectives to evaluate the effectiveness of standard operating procedure (SOP) of LPG filling process, to predict LPG 3 kg sales during 2017-2021, and to evaluate the number of UFM needed by LPG X Depot to fulfill the sales during 2017-2021. The research are descriptive qualitative research. The data regarding the effectiveness of LPG filling process SOP and the capacity of UFM were collected throgh observations; whereas the data regarding the sales of LPG during 2012-2016 was collected through documentation. The data was analyzed descriptively. The results show that: (1) the SOP of LPG filling process is effective with the effectiveness rate about 94.44%, (2) there will be a growth for 8.71% per year in the number of LPG 3 kg sales, and (3) there will be a need to add the number of UFM from 7 unit in 2017 to 16 units in 2021 tofulfill the increase of sales.